Beam characterization and feasibility study for a small animal irradiation platform at clinical proton therapy facilities. (15th December 2020) - Gerlach, S; Pinto, M; Kurichiyanil, N; Grau, C; Hérault, J; Hillbrand, M; Poulsen, P R; Safai, S; Schippers, J M; Schwarz, M; Søndergaard, C S; Tommasino, F; et al.
Abstract: A deeper understanding of biological mechanisms to promote more efficient treatment strategies in proton therapy demands advances in preclinical radiation research. However this is often limited by insufficient availability of adequate infrastructures for precision image guided small animal proton irradiation. The project SIRMIO aims at filling this gap by developing a portable image-guided research platform for small animal irradiation, to be used at clinical facilities and allowing for a precision similar to a clinical treatment, when scaled down to the small animal size. This work investigates the achievable dosimetric properties of different lowest energy clinical proton therapy beams, manipulated by a dedicated portable beamline including active focusing after initial beam energy degradation and collimation. By measuring the lateral beam size in air close to the beam nozzle exit and the laterally integrated depth dose in water, an analytical beam model based on the beam parameters of the clinical beam at the Rinecker Proton Therapy Center was created for the lowest available clinical beam energy. The same approach was then applied to estimate the lowest energy beam model of different proton therapy facilities, Paul Scherrer Institute, Centre Antoine Lacassagne, Trento Proton Therapy Centre and the Danish Centre for Particle Therapy, based on their available beam commissioning data. This comparison indicated similar beam properties for all investigated sites, with emittance values of a few tens of mm·mrad. Finally, starting from these beam models, we simulated propagation through a novel beamline designed to manipulate the beam energy and size for precise small animal irradiation, and evaluated the resulting dosimetric properties in water. For all investigated initial clinical beams, similar dosimetric results suitable for small animal irradiation were found. This work supports the feasibility of the proposed SIRMIO beamline, promising suitable beam characteristics to allow for precise preclinical irradiation at clinical treatment facilities.